Distinctive acoustic changes in speech in Parkinson's disease. (September 2022) - Wang, Meng; Wen, Yanxia; Mo, Shicong; Yang, Liqiong; Chen, Xiaqing; Luo, Man; Yu, Hongdian; Xu, Fan; Zou, Xianwei
Abstract: Dysarthria occurs in the early stage of Parkinson's disease (PD), and the pronunciation of speech sounds is significantly different between PD patients and healthy subjects. However, the formant frequencies of different syllables as vocalized by Chinese PD patients remain unknown. In this study, we recruited 83 PD patients and 44 healthy controls to perform a syllable phonation test. The results revealed that all PD patients presented lower formant frequencies than the control group for various vocalized syllables, presenting a weak correlation with the severity of the disease.